The Effectiveness of Beethoven's Classical Music Therapy (Violin) in Reducing Anxiety in Pregnant Women - Kanata; Raden Maria Veronika Widiatrilupi (KHD Production, 2026)
Anxiety during pregnancy is a common psychological condition that can negatively affect maternal well-being and pregnancy outcomes. Safe and accessible non-pharmacological interventions are therefore needed to help manage maternal anxiety. Music therapy, particularly classical music, has been suggested as a potential method to promote relaxation and emotional regulation. This study aimed to examine the effectiveness of Beethoven’s classical violin music in reducing anxiety levels among pregnant women. A pre-experimental study with a one-group pretest–posttest design was conducted among 30 pregnant women attending antenatal care at a community health center. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS) before and after a 15-minute intervention of listening to Beethoven’s classical violin music. Differences in anxiety scores before and after the intervention were analyzed using a paired sample t-test. The findings demonstrated a significant reduction in anxiety levels following the music intervention. The mean anxiety score decreased significantly after participants listened to Beethoven’s classical violin music (t(29) = 12.819, p < 0.001). Descriptive analysis indicated that most participants experienced a reduction in anxiety severity, shifting from moderate to mild anxiety levels. Listening to Beethoven’s classical violin music significantly reduced anxiety among pregnant women. This intervention is simple, safe, inexpensive, and free from pharmacological side effects, making it a feasible complementary strategy to support psychological well-being in antenatal care settings.